How ready are our students for e-learning? Evidence from Ethiopia - Wondifraw Dejene; Dagmawit Tilahun (Discover Education)
Abstract In the realm of higher education, e-learning has emerged as a game-changer, reshaping the way students engage with their studies. The purpose of this study was examining readiness of higher education students for e-learning. Accordingly, a quantitative research design was employed. The population of the study was higher education students admitted to postgraduate programs. Accordingly, total of 1321 students selected using stratified and simple random sampling techniques participated in the study. A questionnaire consisting of items measuring students’ readiness was employed to collect the data relevant to the study. Descriptive data analysis techniques were employed. The overall results of the study revealed that Ethiopian higher education students were unprepared (M = 2.5 and SD = 1.33) to engage in e-learning system. They preferred the conventional classroom teaching over virtual learning. Furthermore, most of the students were found to be technically poor and had no access to electronic devices which are significant for success in e-learning. They were far behind in most personal and professional requirements. This suggests that Ethiopia has a long way to go to get its postgraduate students ready for an e-learning system.